Effect of intra-vaginal electric stimulation on bladder compliance in stress urinary incontinence patients: the involvement of autonomic tone - Lau, Hui-Hsuan; Lai, Cheng-Yuan; Hsieh, Ming-Chun; Peng, Hsien-Yu; Chou, Dylan; Su, Tsung-Hsien; Lee, Jie-Jen; Lin, Tzer-Bin (Frontiers in Neuroscience, 2024)
Objective In addition to the well-established advantage that strengthened pelvic musculature increases urethral resistance in stress urinary incontinence (SUI) patients, intra-vaginal electrical stimulation (iVES) has been shown in preclinical studies to improve bladder capacity via the pudendal-hypogastric mechanism. This study investigated whether iVES also benefits bladder storage in SUI patients by focusing on compliance, a viscoelastic parameter critically defining the bladder’s storage function, in a clinical study. Moreover, the potential involvement of stimulation-induced neuromodulation in iVES-modified compliance was investigated by comparing the therapeutic outcomes of SUI patients treated with iVES to those who underwent a trans-obturator tape (TOT) implantation surgery, where a mid-urethral sling was implanted without electric stimulation. Patients and methods Urodynamic and viscoelastic data were collected from 21 SUI patients treated with a regimen combining iVES and biofeedback-assisted pelvic floor muscle training (iVES-bPFMT; 20-min iVES and 20-min bPFMT sessions, twice per week, for 3 months). This regimen complied with ethical standards. Data from 21 SUI patients who received TOT implantation were retrospectively analyzed. Mean compliance (Cm), infused volume (Vinf), and threshold pressure (Pthr) from the pressure-flow/volume investigations were assessed. Results Compared with the pretreatment control, iVES-bPFMT consistently and significantly increased Cm (18/21; 85%, p = 0.017, N = 21) and Vinf (16/21; 76%, p = 0.046; N = 21) but decreased Pthr (16/21; 76%, p = 0.026, N = 21). In contrast, TOT implantation did not result in consistent or significant changes in Cm, Vinf, or Pthr (p = 0.744, p = 0.295, p = 0.651, respectively; all N = 21). Conclusion Our results provide viscoelastic and thermodynamic evidence supporting an additional benefit of iVES-bPFMT to bladder storage in SUI patients by modifying bladder compliance, possibly due to the potentiated hypogastric tone, which did not occur in TOT-treated SUI patients. Clinical trial registration:ClinicalTrials.gov, NCT02185235 and NCT05977231.